Management of Post Partum Midwifery Care on the 3rd Day of Mrs "A" with Lack of Breast Milk at Puskesmas Cina - Novianti, Ita; Muchtar, Asrianti Safitri (Jurnal Midwifery, 2025)
Introduction Breast milk is the best food choice for toddlers, because it contains all the nutrients a baby needs in the ideal amount and composition. The process of removing breast milk involves the separation of the hormone oxytocin which aims to stimulate the production of breast milk that has been produced from the breast ducts. Lactation can occur in some mothers both during pregnancy and after delivery. Constraints in expressing breast milk at this early stage can have a negative impact on the baby. In fact, on the most important days of child activity, there is colostrums which has the highest nutritional value among all types of breast milk. Method This study used the Varney and SOAP 7-step midwifery care management method. Result Based on the case studies that have been carried out, it shows that postpartum days from the first to the 7th day are normal and well.Conclusion Case studies by conducting studies in the form of anamnesis and monitoring of post partum mothers on day 3 with insufficient breastfeeding at UPT Puskesmas Cina have carried out studies, analysis, and documentation regarding all actions that have been carried out with the result that no gaps were found between the theory and the cases obtained.